Assessment of Mechanical Properties of Soil-Lime-Crude Oil-Contaminated Soil Blend Using Regression Model for Sustainable Pavement Foundation Construction - Gregory C. Ezeokpube; Isiguzo Edwin Ahaneku; George Uwadiegwu Alaneme; Imoh Christopher Attah; Roland Kufre Etim; Bamidele Charles Olaiya; Iberedem Monday Udousoro (Advances in Materials Science and Engineering)
Oil pollution causes deterioration of the physical, chemical, mechanical, and geotechnical characteristics of affected soil leading to loss of soil productivity for engineering purposes. Different stabilization methods serve as a remedy for such soil to regain its loss engineering properties. This study was concerned with the utilization of lime to stabilize crude oil contaminated soil and to investigate its efficacy for soil stabilization. The study also focused on determining the geotechnical properties of crude oil contamination and matching the result with standard specifications established for engineering works. Hydrated lime, expansive clayey soil, contaminated soil, and potable water were the materials used for the experimental investigation. The contaminated soil was treated with 6.5% lime and 0–20% crude oil contaminated materials obtained from oil exploration sites in North-Eastern Nigeria and per standard test method for laboratory evaluation of consistency limits, compaction properties, California bearing ratio (CBR), and microstructural and mineralogical assessments. The experimental results obtained were further tested statistically through one-way ANOVA and F-statistics to establish the source of variation for the geotechnical properties, while multiple linear regression and correlation statistics helped draw the connection between the consistency limits, compaction, and CBR properties of the soil-lime-COCM blend. Results indicated a coefficient of determination of 99.86. The contaminated soil materials were found to show optimal performance at a 5% ratio and 6.5% of lime for civil construction purposes.